Microsoft and Its Rivals Take 'Office'Politics Global - Forelle, C.; Dias, J. (Wall Street Journal, 2007)
Ente Nazionale Italiano di Unificazione, or UNI, Italy's national standard-setting body, handles such matters as drawing up specifications for water tanks and establishing the proper diameter of nuts and bolts. Its work rarely draws a crowd. That changed this spring when a UNI subcommittee began to consider a bid by Microsoft Corp. to win its support for the file format used in new versions of its ubiquitous Office software. Microsoft is seeking to make that format an international standard for creating and storing computer documents. Within months, a technical committee of some half-dozen members ballooned to no fewer than 85 Italians. Opponents say Microsoft packed the committee with its allies. The Redmond,Wash., giant levels a similar charge at its critics, saying rival InternationalBusiness Machines Corp. is playing the same game in other national committees to block the Office format's approval as a worldwide standard ahead of a key deadline Sunday. That the work of an obscure Italian committee on the codes that tell a computer how to turn bits of data into business letters, spreadsheets and presentations has drawn the feverish attention of technology's largest players speaks to the stakes surrounding Microsoft's delicate pas de deux with governments around the world. Nowhere are those stakes higher than in Europe, where Microsoft awaits a critical court ruling next month in its long-running antitrust battle with European Union regulators.